2020
DOI: 10.3390/cancers12061544
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Signet Ring Cell Adenocarcinomas

Abstract: Signet ring cell adenocarcinomas (SRCCs) are a rare histological subtype of adenocarcinomas with a poor prognosis, typically due to advanced disease at diagnosis. A signet ring cell, mimicking its moniker, contains abundant intracytoplasmic mucin that pushes the nucleus to the periphery. In these cancers, this cell feature comprises more than 50% of the tumor. Despite predilection for the gastrointestinal tract, and in particular the stomach, primary SRCCs are also described in other sites, typically in case r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 40 publications
1
101
1
1
Order By: Relevance
“…CDH1 gastric cancers present as signet-ring cell adenocarcinomas (SRCCs) with abundant intracellular mucin, and readily metastasize before forming significant macroscopic primary lesions, accounting for their typical late stage at detection [ 15 ]. It is not clear either why CDH1 mutations are linked primarily with gastric cancer and an increased risk of lobular breast cancer, although case reports document the co-existence of CDH1 gastric SRCC with colorectal, appendiceal, and pancreatic cancers [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…CDH1 gastric cancers present as signet-ring cell adenocarcinomas (SRCCs) with abundant intracellular mucin, and readily metastasize before forming significant macroscopic primary lesions, accounting for their typical late stage at detection [ 15 ]. It is not clear either why CDH1 mutations are linked primarily with gastric cancer and an increased risk of lobular breast cancer, although case reports document the co-existence of CDH1 gastric SRCC with colorectal, appendiceal, and pancreatic cancers [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its rarity in the lung as a primary tumor, metastatic disease of different organs is considered in the differential diagnosis. The stomach is the most frequent site of origin, 4 but SRCC has also been reported to involve the breast, urinary bladder, thyroid, and ovary. Moreover, malignant lymphomas and melanomas can sometimes exhibit signet‐ring features 5,6 …”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al 6 found “bull's eye” cells, associated with SRCs, in 6.5% of 199 carcinomatous effusions; they were most likely to occur in lobular carcinoma of the breast, followed by bladder, pulmonary, pancreatic, ovarian, gastric and colorectal cancers. Carcinomas with SRC morphology are uncommon, representing about 0.5% of all malignancies 7 . The presence of the SRCs is associated with younger age, higher stage at diagnosis, an aggressive course, and resistance to chemotherapy 7 .…”
Section: Figurementioning
confidence: 99%
“…Carcinomas with SRC morphology are uncommon, representing about 0.5% of all malignancies 7 . The presence of the SRCs is associated with younger age, higher stage at diagnosis, an aggressive course, and resistance to chemotherapy 7 . Signet Ring Cell Carcinoma (SRCC)s represent a variable proportion of adenocarcinomas of various sites, from less than 1% for breast and lung adenocarcinomas, to 5% for appendiceal and 17% for gastric adenocarcinomas 7 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation